2004
DOI: 10.1038/nm1039
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell immunotherapy: mapping the way

Abstract: Dendritic cells (DCs) are the professional antigen-presenting cells of the immune system, with the potential to either stimulate or inhibit immune responses. Exploiting the immune-regulatory capacities of dendritic cells holds great promise for the treatment of cancer, autoimmune diseases and the prevention of transplant rejection. Although early clinical trials indicate that DC vaccines can induce immune responses in some cancer patients, careful study design and use of standardized clinical and immunological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
728
0
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 886 publications
(753 citation statements)
references
References 44 publications
12
728
0
13
Order By: Relevance
“…38 In the clinical trial reported here, the DC viability immediately before injection was homogeneously high (Table 1). Regarding the DC phenotype, we noted considerable interpatient variation in the DC expression of maturation marker CD83 (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…38 In the clinical trial reported here, the DC viability immediately before injection was homogeneously high (Table 1). Regarding the DC phenotype, we noted considerable interpatient variation in the DC expression of maturation marker CD83 (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…Inadequate DC characterization for each included patient has made interpretation and comparison of several previous DC trials difficult. 30 In our previous model systems for DC generation from healthy donors, a high component of CD14 þ cells was not observed. 16 The component of CD14 þ cells found in full-scale prepararations from melanoma patients could be due to a higher concentration of cells during culture.…”
Section: Discussionmentioning
confidence: 88%
“…In a vaccine trial, proper immunomonitoring will be essential, also for interpretation of clinical observations. 30 As responses in this vaccine approach could be directed to any of a broad array of unknown transfected antigens, testing with known melanoma antigens would be of limited value. We will accordingly test primarily for responses against the vaccine itself, using mockDCs as a negative control.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several clinical studies exploit monocyte-derived DC (moDCs) vaccines to induce antigen-specific response in cancer patients. 3 Integrins are transmembrane a/b-heterodimers that regulate cell-cell and cell-extracellular matrix interactions. Lymphocyte function-associated antigen-1 (LFA-1, aLb2) is a leukocyte-specific integrin that mediates firm arrest on the endothelium and, within tissues, cell tethering and the formation of the immunological synapse.…”
mentioning
confidence: 99%